The fingerprint patterns Sumba ethnic population in Tambolaka City, East Nusa Tenggara - Kartika Sari, Nila; Gloriana Gollu , Erliningsih; Rachman Fidiastuti, Hasminar (Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2021)
One of the biological features that humans have is fingerprints. Genetic factors have a role in the formation of fingerprint patterns. In general there are three patterns in the fingerprint that is loop, arch and whorl. The purpose of this research is to know the pattern of fingerprints on Sumba ethnic population in Tambolaka city, East Nusa Tenggara. This research uses qualitative descriptive method because it aims to know the pattern of sidik on Sumba ethnic population. Data collection was done by using documentation, interviews and giving respondents. The research benefits provide information on the pattern of fingerprints on the Sumbanese ethnic population based on the shape of the fingerprint. The sample consists of 56 people. Overall of the patterns contained in the ten fingers of Sumba samples were mostly found in loop patterns with a percentage of 54.41%, whorl patterns 43.97%, and arch patterns of 1.62%. Based on the results of research on the pattern of fingerprints on Sumba ethnic population in Tambolaka the most dominant fingerprint pattern is to have the pattern with the highest order of loops seen on the left thumb, left middle finger and little finger, whorl pattern where this pattern is the highest pattern Second after loop and the third is the arch pattern.